Adaptation of the Eating Expectancy Inventory and Thinness and Restricting Expectancy Inventory to the Turkish, and Examination of Psychometric Properties - Seda Sapmaz Yurtsever; Günay Serap Tekinsav Sütcü (Psikoloji Çalışmaları)
Understanding the cognitive, social, and emotional motivations underlying eating behaviors is important. Equally important, we must recognize eating-related problems sooner and more definitively to develop appropriate intervention programs. In this study, it was aimed to adapt two important inventories into Turkish. The first of these was the Eating Expectancy Inventory (EEI), which evaluates the different expectations underlying eating behavior. Also, adaptation of the Thinness and Restricting Expectancy Inventory (TREI), which evaluates the motivations underlying dietary behavior and thinness, into Turkish was aimed. Following the adaptation, their psychometric properties were examined. The sample consisted of 329 female undergraduate students. In addition to the previously mentioned inventories, Eating Disorder Examination Questionnaire, Three-Factor Eating Questionnaire, Bulimic Investigatory Test Edinburgh, and Palatable Eating Motives Scale were used to test the construct validity of the adapted scales. Confirmatory factor analyses conducted separately revealed that both adapted scales have consistent factor structures with the original formats. For the Turkish form of EEI (T-EEI), five-factor [χ2 (94, N = 329) = 198,71 p <.000, χ2 /df = 2.11, GFI =.93, NFI =.94, CFI = .97 RMSEA=.058]; for the Turkish form of TREI (T-TREI), one factor [χ2 (2, N = 329) = 5,318 p <.000, χ2 /df = 2.66, GFI =.99, NFI =.99, CFI = .99 RMSEA=.071]. Reliability analyses showed that the internal consistency coefficients for the sub-dimensions of T-EEI ranged between .75 and .95, and the test–retest reliability scores ranged between .63 and .83. The study found that the internal consistency coefficient of T-TREI was .98, and its test–retest reliability coefficient was .70. Also, significant positive correlations were found between the scales used to test the construct validity and the measurement tools. Results showed that Turkish version of both inventories had good reliability and valid psychometric properties. Both adapted measures can be used as an effective assessment tool in diagnosing and treating of eating disorders.